Akuntabilitas Publik dan Pengungkapan Laporan Keuangan Pemerintah Daerah (LKPD) di Indonesia - Wiwin Juliyanti (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: Using a quantitative approach at the explanatory level, this research paper aims to examine the effect of the Regional Government Financial Report Disclosure variable on Public Accountability variables. Methodology/approach: The non-probability technique of the purposive sampling type obtained 450 observations from 150 samples of district local governments in Indonesia during 2017-2019 through documentation and literature review of secondary data Results/findings: The results of hypothesis testing using the EViews 9 data processing software provide findings that Disclosure of LKPD (Y) also has a direct effect on Public Accountability. Limitations: The measurement of the Public Accountability variable in this study is based only on audit opinions reported by the Supreme Audit Agency or BPK RI, due to time constraints, this study eliminates the measurement on the weak aspects of the LKPD internal control system as measured by the number of SPI cases and non-compliance with statutory provisions. LKPD invitations as measured by the total cases of non-compliance . Contribution: The implications of these findings explain that disclosure of financial statements can reduce information asymmetry between agents and principals through the publication of financial reports that disclose relevant information. In addition, the research results can become criticism and suggestions for the government as regulators and decision makers in formulating policies related to transparency to the public.